2016
DOI: 10.18632/oncotarget.7324
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes released by granulocytic myeloid-derived suppressor cells attenuate DSS-induced colitis in mice

Abstract: Myeloid-derived suppressor cells (MDSC) have been described in inflammatory bowel disease (IBD), but their role in the disease remains controversial. We sought to define the effect of granulocytic MDSC-derived exosomes (G-MDSC exo) in dextran sulphate sodium (DSS)-induced murine colitis. G-MDSC exo-treated mice showed greater resistance to colitis, as reflected by lower disease activity index, decreased inflammatory cell infiltration damage. There was a decrease in the proportion of Th1 cells and an increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 102 publications
(85 citation statements)
references
References 45 publications
3
81
1
Order By: Relevance
“…Previous studies have demonstrated that statins have therapeutic benefits for the treatment in animal models of autoimmune disease, including inflammatory bowel disease . Intriguingly, a number of studies have shown beneficial effects of MDSCs in treating inflammatory bowel disease (IBD) . We therefore speculated that atorvastatin‐derived G‐MDSCs may reduce the severity of murine experimental colitis.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that statins have therapeutic benefits for the treatment in animal models of autoimmune disease, including inflammatory bowel disease . Intriguingly, a number of studies have shown beneficial effects of MDSCs in treating inflammatory bowel disease (IBD) . We therefore speculated that atorvastatin‐derived G‐MDSCs may reduce the severity of murine experimental colitis.…”
Section: Resultsmentioning
confidence: 99%
“…[20] Cells were removed from culture supernatants by centrifugation at 500 g for 5 min. [20] Cells were removed from culture supernatants by centrifugation at 500 g for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…[16] Researchers have elucidated the complex roles of exosomes in cancer progression. [20] These results drove us to further observe whether MDSCs communicate with CRC cells via exosomes secretion. [19] Especially, S100A9 was abundant in MDSC-derived exosomes.…”
mentioning
confidence: 88%
“…[11] Briefly, cells and cellular debris were removed by sequential centrifugation at 300 × g for 20 min, 1000 × g for 30 min, and 10 000 × g for 30 min. The culture supernatant of CD4 + T cells was harvested.…”
Section: Methodsmentioning
confidence: 99%